2016
DOI: 10.17140/goroj-3-127
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Exposure to Endocrine Disrupting Chemicals Alters the Epigenome: Identification of Reprogrammed Targets

Abstract: Endocrine disruptions induced by environmental toxicants have placed an immense burden on society to properly diagnose, treat and attempt to alleviate symptoms and disease. Environmental exposures during critical periods of development can permanently reprogram normal physiological responses, thereby increasing susceptibility to disease later in life - a process known as developmental reprogramming. During development, organogenesis and tissue differentiation occur through a continuous series of tightly-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 30 publications
1
29
0
1
Order By: Relevance
“…Mild edema in endometrium and moderate edema in perimeter layers of animals which were exposed to low and medium cumin doses, as well as hyperplastic effects in endometrial epithelium of high dose group (Fig 1), confirm the endocrine disruptive effects of cumin essential oil as previous studies in rat revealed the association between early-life exposure to endocrine disruptors and overall size of uterine fibroids (23), (24).…”
Section: Discussionsupporting
confidence: 83%
“…Mild edema in endometrium and moderate edema in perimeter layers of animals which were exposed to low and medium cumin doses, as well as hyperplastic effects in endometrial epithelium of high dose group (Fig 1), confirm the endocrine disruptive effects of cumin essential oil as previous studies in rat revealed the association between early-life exposure to endocrine disruptors and overall size of uterine fibroids (23), (24).…”
Section: Discussionsupporting
confidence: 83%
“…Epigenetic changes have been observed in autism, and these too may be related to environmental agents [12,13] as reported for Bisphenol A and heavy metals (see Table 1) and for flame retardants and other endocrine disruptors, including soy formula and phytoestrogens such as genistein [14][15][16] and also for other nutritional agents such as Vitamin D and folic acid [17][18][19]. However, epigenetics is not the subject of this study, which is limited to the 206 autism-related polymorphic genes reported from gene association studies.…”
Section: Introductionmentioning
confidence: 88%
“…Thalidomide Prenatal use also associated with autistic features [134][135][136] The Dexamethasone treatment during pregnancy in mice ( gestational days [16][17][18][19] increases astrocyte density in the adult offspring Substantia nigra and ventral tegmental area in both males and females and increases tyrosine hydroxylase immunoreactivity in these areas in both sexes, but with a more pronounced effect on Tyrosine hydroxylase positive cell density in females [144]. Ethanol Prenatal use associated with autism [135,145] In utero exposure of mouse progeny to alcohol or methamphetamine causes postnatal neurodevelopmental deficits .…”
Section: Polychlorinated Biphenyls (Pcb)mentioning
confidence: 99%
“…Rats exposed to bisphenol A, an endocrine disrupter found in plastic that binds and activates the nuclear estrogen receptor (ER), during their first five days of life exhibited markedly upregulated expression of the secretaglobin gene in the prostate at day 70. The increased expression correlated with persisting increased enrichment of histone H3K9 acetylation and DNA hypomethylation upstream of the gene’s transcription start site [49, 50]. The adult enzymatic activity of P450s in the liver may also be regulated by epigenetic modifications that are able to be permanently adjusted and established early in life.…”
Section: Neonatal Xenobiotic Exposure and Long-term Epigenetic Alteramentioning
confidence: 99%